Инерционный накопитель энергии электромашинного типа - Чучалин А. И. Александр Иванович; Лоос А. В. Александр Владимирович; Сипайлов Г. А. Геннадий Антонович; Сипайлов В. Г. Владимир Геннадьевич; Горисев С. А. Сергей Алексеевич; Конах А. Д. Алексей Дмитриевич
опубл. 23.05.84